Fruit yield and quality of strawberry plants transformed with a fruit specific strawberry pectate lyase gene. - Youssef, Sabry M.; Jiménez-Bermúdez, Silvia; Bellido, María Luz; Martín-Pizarro, Carmen; Barcelo-Muñoz, Marta; Abdal-Aziz, Samia; Caballero, José Luis; López Aranda, José Manuel; Pliego-Alfaro, Fernando; Muñoz, Juan; Quesada-Felice, Miguel Ángel; Mercado, José A. (Elsevier, 2009)
Two transgenic strawberry lines (Pel 1 and Pel 3) containing the open reading frame of a fruit specific strawberry pectate lyase gene (FaplC) under the control of the CaMV35S promoter have been obtained to evaluate the role of this gene on fruit softening. Ripen fruits from both lines showed a significant downregulation of FaplC, being the percentage of silencing of 84 and 71% on Pel 1 and Pel 3, respectively. The agronomic behaviour of transgenic plants was evaluated during two consecutive years. Fruit set increased in the two transgenic lines when compared with control plants, although Pel 1 showed a significant reduction on fruit weight. Firmness of full ripen fruits from Pel lines was significantly higher than control fruits, while color and soluble solids were not affected. The increase of firmness in Pel lines was maintained when ripe fruits were stored for 3 days at 25 8C. Histological analysis of ripe fruits showed lower intercellular spaces and a higher degree of cell to cell contact area in transgenic fruits when compared with controls. Altogether, these results suggest a direct relationship between pectate lyase gene expression and strawberry fruit softening.
https://openpolicyfinder.jisc.ac.uk/id/publication/16563
Keywords: Fresas - Cultivo; Genetica vegetal; Strawberry; Pectate lyase; Transgenic lines; Cell wall; Fruit firmness